ATM Service Quality Dimensions and Customer Satisfaction: A SEM-Based Study in the Northern Mountainous Region of Vietnam (Architecture Image Studies, 2025)
This study analyzes the impact of ATM service quality on customer satisfaction in the mountainous provinces of Northern Vietnam, where banking infrastructure is limited and ATMs still play an important role in financial access. Based on a survey of 240 customers and applying structural equation modeling (SEM), the study assesses five dimensions: Technological Integration (TI), Proximity & Coverage (PC), Security & Reliability (SR), Personalization (PE), and Eco-Friendliness (EF). The results show that the first four dimensions all have positive and significant impacts on satisfaction, of which Proximity & Coverage is the strongest factor. In contrast, Eco-Friendliness has only a weak impact. This finding is consistent with some recent studies in Thailand, Malaysia, Cambodia, and Indonesia, and adds empirical evidence in the mountainous context of Vietnam. The study contributes to the theory of electronic service quality, and at the same time suggests management implications for commercial banks in expanding their networks, improving reliability, applying technology and gradually implementing green banking.